2020
DOI: 10.1017/cjn.2020.71
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy for Low ASPECTS Large Vessel Occlusion Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: The current American Heart Association guidelines for acute ischemic stroke reserve Grade 1A recommendation for the use of endovascular thrombectomy (EVT) for patients with an Alberta Stroke Program Early Computed Tomography Score (ASPECTS) of ≥6. Objective: We aim to determine the safety and efficacy of EVT for large vessel occlusion ischemic stroke patients with low ASPECTS (5 or less). Methods: Medline, Cochrane Central Register of Controlled Trials, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…Most probably, the different results between this analysis and our study can be explained by the (much) larger sample size (201 vs. 3279 patients) in their analysis. The benefit of EVT in patients with low ASPECTS has been extensively explored in previous studies ( 21 , 22 ). In a subgroup analysis of the MR CLEAN trial, ASPECTS 5-7 was associated with functional outcome (relative to ASPECTS 8-10 and ASPECTS 0-4), however no significant modification of treatment effect by ASPECTS was found ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most probably, the different results between this analysis and our study can be explained by the (much) larger sample size (201 vs. 3279 patients) in their analysis. The benefit of EVT in patients with low ASPECTS has been extensively explored in previous studies ( 21 , 22 ). In a subgroup analysis of the MR CLEAN trial, ASPECTS 5-7 was associated with functional outcome (relative to ASPECTS 8-10 and ASPECTS 0-4), however no significant modification of treatment effect by ASPECTS was found ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, for those patients with ASPECTS <6, the efficacy and safety of EVT is not conclusive. One meta-analysis demonstrated a significant proportion of this subset of patients still achieved good functional outcomes at 90 days and a trend in higher symptomatic intracranial hemorrhage (sICH) among low ASPECTS patients undergoing EVT [4]. More recently, one randomized controlled trial (RCT) from Japan showed that patients with large cerebral infarction had better functional outcomes with EVT than with medical care alone but had more intracranial hemorrhages [5].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized clinical trial data supporting the benefit of endovascular treatment in acute ischemic stroke patients with a large early infarction are not yet available (1). Few retrospective studies exist that suggest a potential positive treatment effect on the functional outcome, as well as procedural safety (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%